WHAT DO THESES AND DISSERTATIONS TELL US ABOUT LEARNING DISABILITIES? - Ceylan, Mustafa; Çetin, Erhan; Karadaş, Cebrail (International Online Journal of Education and Teaching, 2022)
The purpose of this study was to descriptively analyze theses and dissertations written “on learning disabilities. In line with this purpose, keywords such as “specific learning disability”, “specific learning disorder”, “learning disability”, “reading impairment”, “reading disability”, “dyslexia”, “writing impairment”, “writing disability”, “dysgraphia”, “mathematics impairment”, “mathematics disability” and “dyscalculia” were used for the review. The search including the studies published in 2020 put forth 31 master’s theses and 20 Ph.D. However, due to the official restrictions on the studies, the full texts of one master’s thesis and one Ph.D. thesis could not be downloaded. According to the findings, the first master’s thesis was published in 1996, whereas the first Ph.D. dissertation was published in 1998. Written by students from different graduate schools and different departments, these theses and dissertations were gathered around four skill areas. According to the number of theses and dissertations, these skills were reading, mathematics, writing, and science, respectively. Although the increase in the number of the studies written on the subject from different disciplines especially in recent years is considered positive, it is noteworthy that there is no content knowledge in the aforementioned studies conducted outside the special education departments taking into consideration the academic language used and how the study problems are addressed. The theses and dissertations were also explored in terms of participant types, data collection tools, validity-reliability works related to data analysis, and study results. The findings were discussed in the context of developments in the field of special education.